Tahun Yobel dan Harapan - Prayidno, Iswadi (Lux et Sal, 2024)
Pope Francis has proclaimed 2025 as a Jubilee Year, highlighting a profound message of hope, especially amidst the pressing challenges confronting the modern world. The Holy Father invites the faithful to anticipate the good things to come. To better understand its significance, this article aims to explore the biblical roots of the Jubilee Year. The first section examines the possible origins of the Jubilee Year within Jewish tradition. The subsequent section focuses on the specific regulations of the Jubilee Year as outlined in the Book of Leviticus and considers the feasibility of its implementation. It is suggested that the Jubilee Year may not have been fully realizable for the Israelites. Ultimately, Jesus is presented as the one who fulfills the essence of the Jubilee Year.